Low-dose sclerotherapy with lauromacrogol in the treatment of infantile hemangiomas: A retrospective analysis of 368 cases - Wang, Changfeng; Sun, Jiali; Guo, Lei; Song, Dan; Zhang, Xin; Liu, Zhuang; Wang, Liang (Frontiers in Oncology, 2022)
Background: Intralesional injection of lauromacrogol has proven to be an efficient treatment method for infantile hemangioma. This study aims to explore a novel injection therapy and evaluate its efficacy and complications. Methods: The medical records of 464 children with infantile hemangioma who received a lauromacrogol injection from January 2021 to April 2022 were retrospectively analyzed. All patients were reviewed every 4 weeks and assessed according to symptoms and medical records. The patient's age; lesion type, location, size, and thickness; vascular endothelial growth factor level, lesion photographs, ultrasound findings, and complications were recorded. Results: Among the 464 infants who accepted sclerotherapy with lauromacrogol, 305 (65.7%) achieved excellent hemangioma regression. In total, 114 (24.6%) cases achieved good regression, 36 (7.8%) achieved complete moderate regression, and 9 (1.9%) achieved poor regression. The reported incidence of adverse events was 5.6%, and severe complications were not observed. Before and after three courses of treatment, the median vascular endothelial growth factor levels were 104.12 pg/mL and 28.982 pg/mL, respectively. There was a significant difference between the two groups (P=0.0043). Conclusions: The results showed that this novel injection therapy is a safe and effective treatment method. The therapy accelerated the regression of infantile hemangiomas without serious complications.